Endogenous Fluorescent Proteins in the Mucus of an Intertidal Polychaeta: Clues for Biotechnology - Ana P. Rodrigo; Ana Lopes; Ricardo Pereira; Sandra I. Anjo; Bruno Manadas; Ana R. Grosso; Pedro V. Baptista; Alexandra R. Fernandes; Pedro M. Costa (Marine Drugs, 2022)
The vast ocean holds many unexplored organisms with unique adaptive features that enable them to thrive in their environment. The secretion of fluorescent proteins is one of them, with reports on the presence of such compounds in marine annelids being scarce. The intertidal Eulalia sp. is an example. The worm secretes copious amounts of mucus, that when purified and concentrated extracts, yield strong fluorescence under UV light. Emission has two main maxima, at 400 nm and at 500 nm, with the latter responsible for the blue–greenish fluorescence. Combining proteomics and transcriptomics techniques, we identified ubiquitin, peroxiredoxin, and 14-3-3 protein as key elements in the mucus. Fluorescence was found to be mainly modulated by redox status and pH, being consistently upheld in extracts prepared in Tris-HCl buffer with reducing agent at pH 7 and excited at 330 nm. One of the proteins associated with the fluorescent signal was localized in secretory cells in the pharynx. The results indicate that the secretion of fluorescent proteinaceous complexes can be an important defense against UV for this dweller. Additionally, the internalization of fluorescent complexes by ovarian cancer cells and modulation of fluorescence of redox status bears important considerations for biotechnological application of mucus components as markers.